Herpes simplex virus (HSV) suppressive therapy in HSV-2/HIV-1 co-infected women is associated with reduced systemic CXCL10 but not genital cytokines - Andersen-Nissen, Erica (Sex Transm Dis, 2016)
BACKGROUND: Herpes simplex virus type-2 (HSV-2) may heighten immune activation and increase HIV-1 replication, resulting in greater infectivity and faster HIV-1 disease progression. An 18-week randomized, placebo-controlled crossover trial of 500mg valacyclovir twice daily in 20 antiretroviral-naive women co-infected with HSV-2 and HIV-1 was conducted and HSV-2 suppression was found to significantly reduce both HSV-2 and HIV-1 viral loads both systemically and the endocervical compartment. METHODS: To determine the effect of HSV-2 suppression on systemic and genital mucosal inflammation, plasma specimens and endocervical swabs were collected weekly from volunteers in the trial and cryopreserved. Plasma was assessed for concentrations of 31 cytokines and chemokines; endocervical fluid was eluted from swabs and assayed for 14 cytokines and chemokines. RESULTS: Valacyclovir significantly reduced plasma CXCL10 but did not significantly alter other cytokine concentrations in either compartment. CONCLUSIONS: These data suggest genital tract inflammation in women persists despite HSV-2 suppression, supporting the lack of effect on transmission seen in large scale efficacy trials. alternative therapies are needed to reduce persistent mucosal inflammation that may enhance transmission of HSV-2 and HIV-1.